ANALISIS KOMPARATIF HISTORIOGRAFI SIRAH NABAWIYAH KARYA IBNU ISHAQ DAN IBNU HISYAM - Fikri Surya Pratama Pratama (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2022)
This article aims to explain the results of the analysis through a comparison of historiographical works in the form of the Sirah Nabawiyah written by Ibn Ishaq and Ibn Hisham. The research method used is a historical research method with four steps, those are: 1) Heuristics or source collection, the data collection technique used is a literature study by looking for the sirah nabawiyah Ibn Ishaq and Ibn Hisham, as well as books and journal articles relevant to the research. this; 2) Source Criticism; 3) Interpretation or analysis of data, the analysis is carried out in analyzing the selection of sources in making the Sirah Nabawiyah of these two figures, as well as writing the narrative of the sirah whether subjective or objective; 4) Historiography. The results of the study show that the objectivity of historical facts contained in Ibn Ishaq's works is a little weak but his works are perfected by Ibn Hisham's works. In terms of scientific methodology, Ibn Ishaq is not as strong as Ibn Hisham, Ibn Ishaq's sirah nabawiyah, some stories have weak source strengths and are slightly less relevant in some of the contents of his work, through Ibn Hisham many studies of Ibn Ishaq's sirah nabawiyah have been corrected, omitted irrelevant contents and sources and then perfected through the science of hadith transmission. Sirah Nabawiyah Ibn Hisham is the most trusted sirah to date.